Acetylcholinesterase and α-glucosidase inhibitory compounds from Callicarpa maingayi. Issue 17 (19th August 2021) - Ado, Muhammad A.; Maulidiani, M.; Ismail, Intan Safinar; Ghazali, Hasanah M.; Shaari, Khozirah; Abas, Faridah
Abstract: Phytochemical investigation on the soluble fractions of n -hexane and dichloromethane of methanolic leaves extract of the Callicarpa maingayi K. & G. led to the isolation of three triterpenoids [euscaphic acid (1 ), arjunic acid (2 ), and ursolic acid (3 )] together with two flavones [apigenin (4 ) and acacetin (5 )], two phytosterols [stigmasterol 3- O -β-glycopyranoside (6 ) and sitosterol 3- O -β-glycopyranoside (7 )], and a fatty acid [ n -hexacosanoic acid (8 )]. Six (6) compounds (1, 2, 3, 4, 5, and 8 ) are reported for the first time from this species. Their structures were elucidated and identified by extensive NMR techniques, GC-MS and comparison with the previously reported literature. Compound 3 was found to displayed good inhibition against acetylcholinesterase with an IC50 value of 21.5 ± 0.022 μM, while 1 and 2 exhibited pronounced α-glucosidase inhibitory activity with IC50 values of 22.4 ± 0.016 μM and 24.9 ± 0.012 μM, respectively. Abstract : UF0001